Skeletal Side Effects of Systemic Isotretinoin Treatment: Do They Depend on Age, Gender, Treatment Duration, Daily Dose and Isotretinoin-Naiveness? - Defne Özkoca; Nazlı Caf; Nazan Nur Alacagöz Yılmaz; Tuğba Kevser Uzunçakmak; Ayşenur Özdil; Ayşe Nilhan Atsü (Mattioli1885, 2023)
Introduction: Systemic isotretinoin is the most effective treatment modality in acne vulgaris; however, both patients and physicians hesitate to use it due its side effects. Objectives: The aim of this study is to determine the prevalence of fatigue, myalgia and low back pain during systemic isotretinoin treatment; and to determine their relationship with age, gender, treatment duration, daily isotretinoin dose and isotretinoin-naiveness of the patient. Methods: This is a cross sectional study including the acne vulgaris patients, aged between 13 to 40 years, who have at least received one month of oral isotretinoin treatment. Patients were questioned for side effects during their follow-up visits; a physical therapy and rehabilitation specialist further evaluated patients complaining of low back pain. Results: Fatigue was reported by 4.4% of the patients, myalgia by 2.8% and low back pain by 25% of the patients; 2.2% had inflammatory and 22.8% had mechanical low back pain. None of the patients had sacroiliitis. All the side effects that were examined were found to be independent of age, gender, isotretinoin dosage (mg/kg/day), treatment duration and isotretinoin-naiveness. Conclusions: The side effects are not as common as feared; thus, patients and physicians should not hesitate to use systemic isotretinoin in indicated cases.